Ground magnetic field fluctuations associated with pulsating aurora. Issue 10 (30th October 2015) - Michell, R. G.; Samara, M.
Abstract: A case study of an intense pulsating auroral event is presented where the large‐scale (100–200 km) optical intensity variations are anticorrelated with fluctuations in the ground magnetometer data at a frequency of 0.1 Hz. The auroral event occurred over Poker Flat, Alaska, on 1 March 2012 and was imaged optically with several different fields of view and filters. The fluctuations in the magnetometer data were most prominent in the D component and had magnitudes of 1 to 5 nT. The auroral intensity variations had amplitudes of 200 to 400 R, comprising 25% to 50% of the total auroral luminosity at 427.8 nm. The direction of the magnetometer deflections is consistent with a south‐to‐north ionospheric current present when each pulsation is on, thus providing closure for the field‐aligned currents associated with each of the pulsating patches. Key Points: Pulsating aurora has field‐aligned current that closes through the ionosphere The 0.1 Hz signals are in both pulsating aurora and the ground magnetic field The optical and magnetic field variations are exactly out of phase